Test study on the influences of dynamic stress and load history to the dynamic properties of the remolded red clay (2016)
The dynamic properties of subgrade materials are critical factors affecting stability within the traffic engineering discipline. Remolded red clays are frequently used as subgrade filling materials, however, to date, a paucity of data exist on to the dynamic properties of this material. Accordingly, a large number of dynamic triaxial tests under cyclic loads were carried out to quantify the suitability of remolded red clay as subgrade filling. Several potentially influencing dynamic factors were considered, including dynamic stress, vibration frequency, consolidation confining pressure, consolidation ratio and compactness. Plastic strain and dynamic strength curves of remolded red clays under varying dynamic loads and load histories have been developed, in addition to the inclusion of those influencing factors. Test results show that within the range not exceeding the inherent strength of the test samples, increases soil compactness, confining pressure, and vibration frequency serves to enhance overall dynamic power in concurrence with retarding the development of accumulated plastic strain. Conversely, an improvement in the amplitude of the dynamic stress and consolidation ratio was shown to cause a decrease in dynamic strength and acceleration in the development of accumulated plastic strain. An empirical equation relating critical dynamic strength and load histories of remolded red clay has been developed for the provision of fundamental reference data for future studies. Pruebas sobre la influencia de la carga dinámica y la historia de carga en las propiedades dinámicas de arcilla roja reestructurada ResumenLas propiedades dinámicas de los materiales de base son factores cruciales que afectan la estabilidad en la ingeniería de tráfico. La arcilla roja reestructurada se utiliza frecuentemente como material de relleno de bases, sin embargo, hasta la fecha, existe una escasez de información sobre las propiedades dinámicas de este material. De acuerdo con esto, se realizó un gran número de pruebas triaxiales dinámicas bajo cargas cíclicas para cuantificar la pertinencia de la arcilla roja reestructurada como material de relleno en bases. Se consideraron varios factores dinámicos que podrían ser determinantes, como la fuerza dinámica, la frecuencia de vibración, la presión de confinamiento, el índice de consolidación y la compactibilidad. Se desarrollaron las curvas de fuerza plástica y dinámica de arcilla roja reestructurada con varias cargas dinámicas e historia de cargas, además de la inclusión de los factores determinantes. El resultado de las pruebas muestra que dentro del rango de la fuerza inherente a las muestras de estudio, el incremento de la compactibilidad del suelo, la presión de confinamiento y la frecuencia de vibración sirven para mejorar, en general, el poder dinámico al tiempo que retrasa el desarrollo de la fuerza plástica. Al contrario, el mejoramiento de la amplitud de la fuerza dinámica y el índice de consolidación muestra una reducción en la fuerza dinámica y una aceleración en el desarrollo de la fuerza plástica acumulada. Finalmente, se desarrolló una ecuación empírica que relaciona la fuerza dinámica crítica y las cargas históricas de arcilla roja reestructurada con el fin de proveer información de referencia para estudios futuros.